Analysis of Factors Affecting the Net Asset Value of Sharia Equity Mutual Funds - Nurdiansyah Putri Purnamasari; Muhammad Hafizh (eCo-Buss, 2025)
One type of collective investment vehicle that manages public monies for investment is a sharia stock mutual fund stocks that are in accordance with sharia law and avoid transactions that contain elements of usury, maisir, and gharar. This study aims to investigate how the money supply, inflation, gold prices, and age of mutual funds impact the performance of Indonesian mutual funds' net worths that invest in sharia stocks between 2019 and 2024. This study made use of secondary data study. The sample used in this study was 6 sharia stock mutual fund companies, using purposive sampling techniques and there was a population of 55 sharia stock mutual funds. Using Eviews 12 sv software, utilizing the panel data regression approach, was used to secondary data. The findings of the study indicate that the quantity of currency in use, the cost of gold, and the age of mutual funds all have a major influence on the value of net assets (NAV) of Indonesian Sharia Equity Mutual Funds, however inflation has no discernible effect on this number.